2013
DOI: 10.1590/s0103-84782013005000107
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-physical processes and soil properties correlated with origin of soil hydrophobicity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Hydrophobic compounds that promote changes of soil sorptivity indirectly clearly affect water infiltration processes (Vogelmann et al, 2013a). According to the definition of Philip (1957) the sorptivity expresses the tendency of an intrinsic material to absorb and transmit a liquid by capillarity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic compounds that promote changes of soil sorptivity indirectly clearly affect water infiltration processes (Vogelmann et al, 2013a). According to the definition of Philip (1957) the sorptivity expresses the tendency of an intrinsic material to absorb and transmit a liquid by capillarity.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that hydrophobicity is a much broader phenomenon than previously assumed (Hallett and Young, 1999;Vogelmann et al, 2012), and highlighted the need to study about its temporal and spatial properties, factors, and impacts of soil hydrophobicity on hydrological cycle. In this context, aggregate behavior in soil matrix is crucial to understanding changes in soil infiltration from fluctuating soil wettability (Ritsema et al, 1998;Vogelmann et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, decreasing MC PS with increasing OM% relates to increased pore space due to OM-facilitated soil granulation (Han et al, 2006). There is also the possibility of decreasing MC PS due to increasing hydrophobicity as OM-containing soils dry out (Vogelmann et al, 2013). In contrast, the increasing MC PS trend with increasing Sand% may be due to preferential pore space saturation in sandier topsoil portions.…”
Section: General Observations and Trendsmentioning
confidence: 99%
“…This is a global phenomenon, which affects infiltration as well as soil water retention and plant growth. Hydrophobicity can be responsible for enhanced surface runoff, erosion and preferential flow (VOGELMANN et al, 2013b). Due to this high relevance, a great number of studies have been conducted on possible causes of water repellency and the results point to a variety of factors causing and influencing soil water repellency (SCHAUMANN et al, 2007;DOERR et al, 2007 Records of hydrophobic soils in Brazil are found mainly in areas cultivated with woody species and grasses (VOGELMANN et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…These substances may be of various origins; most of them derived from local vegetation due to hydrophobic organic compounds in their chemical composition and are released either by deposition or decomposition of plant material (DOERR et al, 2007). Hydrophobicity is found to be related with other factors such as soil moisture (DOERR et al, 2007), pH (MATAIX-SOLERA et al, 2007), soil particle size (VOGELMANN et al 2013b), incidence of fires (VOGELMANN et al, 2012), and presence of some fungi and bacteria species (SCHAUMANN et al, 2007).…”
Section: Introductionmentioning
confidence: 99%